2022
DOI: 10.1007/s40273-021-01121-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Humanistic Burden of Triple-Negative Breast Cancer: A Systematic Literature Review

Abstract: Background Triple-negative breast cancer (TNBC) accounts for 10-20% of all breast cancers (BCs). It is more commonly diagnosed in younger women and often has a less favorable prognosis compared with other BC subtypes.Objective The objective of this study was to provide a literature-based extensive overview of the economic and humanistic burden of TNBC to assist medical decisions for healthcare payers, providers, and patients. Methods A systematic literature review was performed using multiple databases, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
(162 reference statements)
0
16
0
1
Order By: Relevance
“…An SLR of 19 studies published between 2016 and 2021 reported significant reductions in Functional Assessment of Cancer Therapy—Breast scores in patients with TNBC compared to those with non-TNBC [ 17 ]. Furthermore, a clinically meaningful decrease in mean utility values was reported in patients experiencing a progressed disease state (EQ-5D-3L index 0.601) compared to those in a progression-free state (EQ-5D-3L index 0.715) [ 17 ]. Pembrolizumab was found to improve HRQoL relative to chemotherapy in PD-L1–positive patients with metastatic TNBC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An SLR of 19 studies published between 2016 and 2021 reported significant reductions in Functional Assessment of Cancer Therapy—Breast scores in patients with TNBC compared to those with non-TNBC [ 17 ]. Furthermore, a clinically meaningful decrease in mean utility values was reported in patients experiencing a progressed disease state (EQ-5D-3L index 0.601) compared to those in a progression-free state (EQ-5D-3L index 0.715) [ 17 ]. Pembrolizumab was found to improve HRQoL relative to chemotherapy in PD-L1–positive patients with metastatic TNBC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is associated with a substantial economic burden that is largely driven by high treatment costs. A systematic review conducted in 2023 demonstrated substantial variation in the proportion of total cancer care costs attributable to anticancer drugs, from 7.5% (systemic therapies) to 75% (targeted therapy [bevacizumab]) [ 17 19 ]. For immune checkpoint inhibitors, a retrospective analysis of United States (US) Medicaid files demonstrated an increase in expenditure from 2.8 million US dollars (USD) (~2.58 million Swiss francs [CHF]) in 2011 to USD4.1 billion (CHF~3.78 billion) in 2021 across all cancer types [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With 19.3 million new cases and 10 million deaths in 2020, cancer is a leading cause of premature death and a significant barrier to increasing life expectancy for the global population ( 1 , 2 ), and results in high social medical expenses and personal financial burden ( 3 , 4 ). To date, cancer remains a major public problem that threatens the health of the population.…”
Section: Introductionmentioning
confidence: 99%
“…The global incidence of breast cancer in women is estimated to reach as many as 3.2 million new cases annually by the year 2050 [ 2 ]. Breast cancer is the fifth leading cause of cancer deaths worldwide and is estimated to have caused 684,996 deaths in 2020 [ 3 ]. Incidence rates for breast cancer far exceed those of other cancers in both transitioned (55.9 per 100,000) and transitioning (29.7 per 100,000) countries [ 1 ].…”
Section: Introductionmentioning
confidence: 99%